Cord-Blood High-Sensitivity Troponin-I Reference Interval and Association with Early Neonatal Outcomes - Mondal, Tapas; Ryan, Paul M.; Gupta, Kaaran; Radovanovic, George; Pugh, Edward; Chan, Anthony K. C.; Hill, Stephen (American Journal of Perinatology, 2021)
Objective This study was aimed to establish a reference interval for high-sensitivity cardiac troponin I (hs-cTnI) in umbilical cord blood of infants and to assess its association with the risk of predetermined early neonatal outcomes in a high-acuity tertiary care hospital.Study Design Umbilical cord-blood samples were collected and hs-cTnI was measured in all infants born between August 2015 and September 2015 at McMaster Children's Hospital (n = 256). Gestational age, birth weight, Apgar's scores, age in days at which feeding was established, neonatal intensive care unit (NICU) admission, and discharge in days after birth were recorded.Results The 90th, 95th, and 99th percentiles for the term infant subcohort were 19.75, 41.45, and 166.30 ng/L, respectively. We observed decreased mean gestational ages and birth weights in both the 90th (37.7 weeks; 2,961.4 g) and 95th percentiles (37.1 weeks; 2,709.9 g) when compared with the remaining infants. Moreover, levels of hs-cTnI were significantly higher in infants with respiratory distress requiring intervention (p < 0.05), low birth weight infants (p < 0.01), preterm infants (p < 0.001), and those requiring NICU admission (p < 0.01). Multiple linear regression of the recorded demographic factors revealed prematurity (gestational age <35 weeks: coefficient 0.346 ± 0.160, p < 0.05; gestational age <37 weeks: coefficient 0.253 ± 0.105, p < 0.05) and male sex (coefficient 0.138 ± 0.047; p < 0.01) to be most predictive of log-hs-cTnI levels.Conclusion This study establishes the reference values for cord-blood hs-cTnI in infants at a tertiary care center. Premature and sick infants requiring NICU admission had significantly higher levels of hs-cTnI.Key Points
Keywords: neonatal; umbilical cord blood; high-sensitivity troponin I; reference interval